Narrative about President Prabowo Subianto on Instagram Account @gerindra (Narrative Network Analysis) - Karina Febriana; Ririt Yuniar (CV. Media Digital Publikasi Indonesia, 2026)
There appears to have been a shift in public opinion regarding President Prabowo’s Leadership. This study examines the network of public narratives about President Prabowo formed in the comments section of the official Instagram account @gerindra. With increased public discussion about the performance of the Prabowo-Gibran administration, Instagram has become the main space for the public to express opinions, offer suggestions, and evaluate government policies. This study aims to analyze the public narrative network in the comments section of the @gerindra Instagram account. It uses a post-positivist paradigm with a mixed-methods approach and analyzes three posting periods (November 15, 2023), the election period (February 17, 2024), and one year in office (October 20, 2025). Data were collected using IGcomment.com; dominant narratives were mapped using Voyant Tools; narrative forms were examined using Nvivo; and narrative networks were visualized using Gephi 0.10.1. The results show that public narratives change over time and across political situations, and that key actors construct narrative content in the comment section. These findings indicate that the Instagram comment section @gerindra is the leading platform for the public to build narratives and opinions, as well as evaluate government performance. Further research is expected to discuss the habits of social media users through the actors involved.